Investigating the Potential interventions and policy Recommendations for Reducing Criminal Recidivism: Qualitative study in the Eastern Cape, South Africa - Dwabayo, Luphumzo; Odularu , Oluwayemi IbukunOluwa (Journal of Ecohumanism, 2025)
Purpose: the purpose of this paper is to identify potential interventions and policy recommendation for criminal recidivism in Chris Hani community, Eastern Cape, South Africa. This paper endeavors to combat re-offending whilst affording offenders the opportunity to prove that they are worthy of the trust of the community. Containment theory: The study is grounded in Containment. This theory uses two reinforcing structures such as inner containment and outer containment, which posits that both internal and external factors influence an individual's ability to resist criminal behaviour. Provides a basis for designing interventions that strengthen personal and social containment mechanisms to minimize the likelihood of re-offending. These two structures also act as buffer or insulator between the individual and deviant behavior. Sample size: Sample size of 30 respondents of which 15 are males and 15 females was carefully selected from Chris Hani X-convicts to represent the whole population. Data collection method: semi-structured interviews were used as primary data collection method for the study. Research design: the study adopted observational research design which allows the researcher to study and measure variables of interest in their natural settings without directly intervening in participant’s lives. Delimitations to the study: Delimitations of the study involve geographic scope, timeframe, participant demographics and ethical considerations.